Dynamic approach to sound pitch - RYFFERT, Halina; CZAJKOWSKA, Alicja; JORASZ, Urszula; MAKAREWICZ, Rufin (Archives of Acoustics, 1979)
Theoretical considerations have provided an analytical expression describing simultaneous changes of the intensity and pitch of the signal emitted by a moving source. Experimental investigations of the perceptibility of the sound-pitch changes accompanied simultaneously by appropriate intensity changes have confirmed mutual coupling of these two quantities in the process of the formation of a general sonic impression. A qualitatively new effect of automasking has been observed and shown to consist in an interaction of the two varying psychoacoustic parameters in the process of sound perception.